The Relationship between Motivation, Attitude, Learning Style and English Grammatical Competence of Higher Education Students - Marghany, Marghany Mahmoud (2000)
The purpose of the present study was to examine performance of UPM freshmen in English grammar according to motivation, attitude, and learning style (Le. tolerance of ambiguity) on the one hand and according to gender, socioeconomic status, location, and exemption status on the other. Based on Dunkin and Biddle's model, tolerance of ambiguity is classified as one of the process variables, while the other six independent variables come under the category of context variables. The samples of the present study comprised 349 freshmen at Universiti Putra Malaysia. The samples enrolled in May semester 1998. The samples were divided into 227 non-exempted students and 122 exempted students. The non-exempted students, unlike the exempted students, were required to sit for one of the English proficiency courses administered by the Faculty of Modem Languages Studies (i.e. BB12401, BB12402, BBI2403). The 227 non-exempted students included 100 students from BB12401, 47 students from BB12402, and 80 students from BB12403. The 122 exempted students comprised 72 students from the Faculty of Medicine, 30 TESL students from the Faculty of Educational Studies, 12 students from the Faculty of Veterinary, and 8 students from the Faculty of Forestry. Written data were collected through selected instruments, namely (1) discrete-point exercises both multiple choice and fill-in-the blank, (2) grammaticality judgment exercises, (3) translation-based task, (4) two sets of structured questionnaire adopted from Noran Fauziah Yaakub, Habibah Elias, Rahil Mahyuddin, Hajjah Nora Mohd. Nor and Mohd. Faiz Abdullah (1993a) for attitude (34 items) and for motivation (31 items), and (5) 12 item questionnaire for learning style; which was developed based on Christopher Ely's second language tolerance of ambiguity scale (Reid, 1995).